Using the Think Pair Share Cooperative Learning Model for Increase Skills Think Critical Student Class V Elementary School - Azzahra, Vina Siti; Arga, Hana Sakura Putu; Nurfurqon, Faridillah Fahmi; Murni, Sukma (Kopertis Region IV Jabar and Banten, 2024)
This research is entitled using the Think Pair Share cooperative learning model to improve the critical thinking skills of fifth grade elementary school students. This aim is to improve students' critical thinking skills, and students' responses to social studies learning material on Indonesian Community Economic Activities using the Think Pair Share (TPS) type cooperative learning model. This research uses a Mix Method or often called mixed method research between qualitative and quantitative, the design used is explanatory sequential. Data collection in this research used test, observation, interview and questionnaire techniques. In this study, the population taken was elementary school VC class students located at SD Negeri Cicalengka 03, totaling 39 students consisting of 13 male students and 26 female students. The results of data processing show that the average score obtained can be proven by the average result of the pretest class which was not given the TPS learning model getting an average score of 62.41 and the score obtained by the posttest class getting an average score of 86.28. The conclusion of this research can be interpreted as that Think Pair Share is more effective in improving the critical thinking power of fifth grade elementary school students.